Characteristics of changes in sport karate - Nešić Milan (University Educons, Faculty of Sports and Tourism, Novi Sad, 2018)
Causes of organizational changes in sports are dominantly conditioned by changes in environment - external and internal. Because of that, the main goal of changes in sport karate needs to lie in reshaping sports (karate) organisation in a way which would also allow for achieving "internal and external harmony", i.e. improvement of overall organisational performance (regardless of whether that organization is club or association) which will have appropriate capacity to efficiently and effectively adapt to changes in the environment. One of the changes which can be considered "radical" in the context of sport Karate is decision of the International Olympic Committee that karate, as defined by the organizational concept of WKF, be included in the programme of Olympic Games in Tokyo 2020. This is an important factor which directs changes in the system of our sport Karate (in Serbia and Vojvodina). Because of that, karate in Vojvodina faces a usual managerial dilemma related to the period and manner of introduction of changes, i.e. answer to the question - how to start? Every organization or individual, in accordance with environment and context of change inclusion, reacts in different ways. Every authenticity of change is conditioned by "throughput" of a greater number of internal and external elements of a karate organisation. Because of that, essential assumption for a correct answer to the question asked lies in quality and responsible mutual cooperation of people in organisations. This cooperation is also based on testing of different ideas, communication in the function of constructive debate about problems, creation of authentic (personal) models of changes and adoption of appropriate strategies. One of the first steps in strategic directing of changes in karate is, surely, a studious and detailed analysis of the sport karate environment. This paper, essentially, presents a shorter theoretical analysis and an explication of basic factors which have defined the development of karate in Vojvodina, as an assumption (a hypothetical frame) for more complex future analyses of sport karate environment, necessary for the preparation and creation of strategic documents for development of karate as an Olympic sport.